Catalpol ameliorates CFA-induced inflammatory pain by targeting spinal cord and peripheral inflammation - Zhao, Baoxia; Fu, Jie; Ni, Huadong; Xu, Longsheng; Xu, Chengfei; He, Qiuli; Ni, Chaobo; Wang, Yahui; Kuang, Jiao; Tang, Mengjie; Shou, Qiyang; Yao, Ming (Frontiers in Pharmacology, 2022)
Chronic, inflammatory pain is an international health concern that severely diminishes individuals' quality of life. Catalpol is an iridoid glycoside derived from the roots of Rehmannia glutinosa that possesses anti-inflammatory, antioxidant, and neuroprotective properties for the treating multiple kinds of disorders. Nevertheless, catalpol's impacts on inflammatory pain and its potential methods of action are still unclear. The purpose of this investigation is to determine the mechanism of catalpol to reduce the inflammatory pain behaviors in a rat model with complete Freund's adjuvant (CFA). Catwalk, Von-Frey, and open field testing were performed for behavioral assessment. Western blot analysis and real-time quantitative PCR (RT-PCR) were employed to identify variations in molecular expression, while immunofluorescence was utilized to identify cellular localization. Catalpol effectively reduced CFA-induced mechanical allodynia and thermal hyperalgesia when injected intrathecally. Moreover, catalpol can regulate the HDAC4/PPAR-γ-signaling pathway in CFA rat spinal cord neurons. Meanwhile catalpol significantly decreased the expression of the NF-κB/NLRP3 inflammatory axis in the spinal cord of CFA rats. In addition, both in vivo and in vitro research revealed that catalpol treatment inhibited astrocyte activation and increase inflammatory factor expression. Interestingly, we also found that catalpol could alleviate peripheral pain by inhibiting tissue inflammation. Taken together, the findings declared that catalpol may inhibit inflammatory pain in CFA rats by targeting spinal cord and peripheral inflammation..